Observed ground deformation during the Krafla eruption of March 16, 1980 - Tryggvason, Eysteinn (Universidade dos Açores, 1982)
International Symposium on the Activity of Oceanic Volcanoes. Ponta Delgada, 4-9 August 1980. The Krafla volcano has been monitored with continuously recording tiltmeters and seismometers and frequent geodetic measurements since the beginning of the present episode of activity in 1975. The inflation-deflation sequence of the volcano showed striking regularity in 1977 and 1978 but it became more erratic in late 1979 with slow inflation interrupted by small deflations. The eruption of March 16, 1980 was preceded by rapid deflation which started at 15:15 (GMT) and intense volcanic tremor started simultaneously. The subsidence became very rapid at about 16:00, about three times more rapid than had been seen in any previous subsidence event. The eruption was first seen at about 16:20, but it may have started 10 to 20 minutes earlier. It lasted until about 22h that same night. The deflation of the volcano ceased at about 03h next morning, March 17, and a new inflation started within a few hours. Tilt observations indicate that roughly 30 x 106m3 of magma left the Krafla magma chamber, but only some 10 % of this carne to the surface as very fluid basaltic lava. New fissures extended through the Krafla volcano over a distance of a:bout 21 km and the widening od' the fissure zone was about 1.5 m. info:eu-repo/semantics/publishedVersion